1979
DOI: 10.1007/bf01219798
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic preservation of isolated rat Islets of Langerhans: Effect of cooling and warming rates

Abstract: Isolated rat Islets of Langerhans have been frozen to and stored at -196 degrees. After thawing, these islets were capable of secreting near normal levels of insulin in response to graded glucose challenge. Maximal retention of functional viability as measured by the ability of the islets to secrete insulin in response to a glucose challenge was obtained after freezing islets at a cooling rate of approximately 75 degrees per minute in the presence of 1.0 mol/1 dimethyl sulfoxol followed by warming at rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Long Evans Hooded (LEH) male rats (220-250 g) were fast-H. L. Bank: Fluorescent islet cell viability assay ed for 12 to 18 h before the isolation of the islets. Pancreatic islets of Langerhans were isolated using the collagenase isolation procedure described previously [13,14]. A single step, 11% Ficoll (LSM, Bionetics Lab, Litton, Kensington, Md, USA) separation was used to separate islets from the tissue digest [14].…”
Section: All National Institute Of Health and Institutional Animal Rementioning
confidence: 99%
See 1 more Smart Citation
“…Long Evans Hooded (LEH) male rats (220-250 g) were fast-H. L. Bank: Fluorescent islet cell viability assay ed for 12 to 18 h before the isolation of the islets. Pancreatic islets of Langerhans were isolated using the collagenase isolation procedure described previously [13,14]. A single step, 11% Ficoll (LSM, Bionetics Lab, Litton, Kensington, Md, USA) separation was used to separate islets from the tissue digest [14].…”
Section: All National Institute Of Health and Institutional Animal Rementioning
confidence: 99%
“…Pancreatic islets of Langerhans were isolated using the collagenase isolation procedure described previously [13,14]. A single step, 11% Ficoll (LSM, Bionetics Lab, Litton, Kensington, Md, USA) separation was used to separate islets from the tissue digest [14]. The islets were collected at the buffer/ficoll interface, and washed with phosphate buffered saline (PBS).…”
mentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO) was chosen as the cryoprotectant in this study (22), and two methods for exposing the tissue to DMSO (2 M) before freezing were compared. The first, based on the method of Rajotte et al (27), involves a much longer prefreeze exposure to the cryoprotectant solutions (45 min) than does the second (6 min), which is based on the method of Bank et al (18). The first method probably allows time for full permeation of the cryoprotectant into the tissue, whereas the second does not (9).…”
Section: Methodsmentioning
confidence: 99%
“…Banks et al [272] found that freezing in 1 mol/1 DMSO at 75 ~ gave optimal viability by in vitro parameters. Rajotte et al [275] found different conditions to be optimal: stepwise suspension in 2 mol/1DMSO, seeding with ice at -7.5 ~ freezing to -75 ~ at 0.25 ~ min, storage at -196 ~ and warming at 7.5 ~ Bretzel et al [276] have also normalized blood glucose in diabetic rats with isologous islets frozen in 1 mol/1 DMSO at 2 ~ and stored for 4 weeks at -196 ~ before rapid thawing and intraportal transplantation.…”
Section: Cryopreservation Of Islet Tissue a Variety Of Cells Ormentioning
confidence: 99%
“…Several investigators have used in vitro tests to determine the optimal conditions for freezing and thawing of adult islets [271,272] or fetal rat pancreas [273]. Critical factors include the cooling and warming rates, the concentration and penetration of agents added to protect against intracellular ice crystal formation, and the osmatic changes that occur during removal of the cryoprotectant [270].…”
Section: Cryopreservation Of Islet Tissue a Variety Of Cells Ormentioning
confidence: 99%